How Resilient Was Trade to COVID-19 ? - Bas, Maria (World Bank, Washington, DC, 2022)
This paper examines which product supply-side characteristics affect the resilience of traded products to the COVID-19 pandemic. Relying on monthly product-level exports by all countries to the United States, Japan, and 27 European Union countries from January 2018 to December 2020, the paper estimates a difference-in-differences specification for the impact of COVID-19 incidence (deaths per capita) mediated by product characteristics, accounting for when exports reach their destination by relying on product transportation lags. Higher reliance on foreign inputs, China as an input supplier, and unskilled labor and a lower degree of complexity negatively affected exports as a result of COVID-19.